2002
DOI: 10.1016/s0749-3797(02)00449-x
|View full text |Cite
|
Sign up to set email alerts
|

Reviews of evidence on interventions to prevent dental caries, oral and pharyngeal cancers, and sports-related craniofacial injuries1 1The names and affiliations of the Task Force members are listed at the beginning of this supplement, and at www.thecommunityguide.org.

Abstract: This report presents the results of systematic reviews of effectiveness, applicability, other positive and negative effects, economic evaluations, and barriers to use of selected population-based interventions intended to prevent or control dental caries, oral and pharyngeal cancers, and sports-related craniofacial injuries. The related systematic reviews are linked by a common conceptual approach. These reviews form the basis of recommendations by the Task Force on Community Preventive Services (the Task Forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(50 citation statements)
references
References 126 publications
2
44
0
Order By: Relevance
“…The median attack rate (8%) for the six studies used to estimate economic benefit per tooth was lower than the cost-saving threshold attack rate of 12% (i.e., annual caries increment of 0.47 surfaces for four molars 13 ) found in the 2002 economic review. Possible reasons for a higher cost-saving threshold attack rate in the 2002 review are that among the three studies that found positive net costs, one reported sealant times per child exceeding 1 hour and used an early sealant material excluded in the recent effectiveness review 56 and the two remaining studies did not include productivity losses in estimating the economic benefit.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The median attack rate (8%) for the six studies used to estimate economic benefit per tooth was lower than the cost-saving threshold attack rate of 12% (i.e., annual caries increment of 0.47 surfaces for four molars 13 ) found in the 2002 economic review. Possible reasons for a higher cost-saving threshold attack rate in the 2002 review are that among the three studies that found positive net costs, one reported sealant times per child exceeding 1 hour and used an early sealant material excluded in the recent effectiveness review 56 and the two remaining studies did not include productivity losses in estimating the economic benefit.…”
Section: Discussionmentioning
confidence: 66%
“…The economic review included six studies conducted from the early 1970s to 1999. 13 Many factors that can influence the cost and benefit of SSPs have changed since this earlier economic review. These include:

decrease in caries prevalence 14 ;

increase in number of states allowing dental hygienists working in SSPs to assess a child’s need for sealants and to place sealants without a dentist being present 15 ; and

increased prevalence of sealants among children 14,16 and SSPs that target high-risk schools.

…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of the cost-effectiveness and applicability of screening failed to find sufficient evidence "to determine public health relevance in controlling morbidity, mortality, or quality of life" [19]. However, a recent study suggests that visual inspection of the mouth could reduce mortality from oral cancer [20].…”
Section: Resultsmentioning
confidence: 99%
“…According to Truman, Gooch & Sulemana [21] cavities are the 4 th most expensive disease in the United States. Dental emergencies are also noted to be the second leading cause of outpatient surgeries at children's hospital [22].…”
Section: Economic Burdenmentioning
confidence: 99%